Optimisation of the Quantification of Total Soluble Solids, pH and Titratable Acidity in South African Grape Must using Fourier Transform Mid-infrared Spectroscopy - Swanepoel, M.; du Toit, M.; Nieuwoudt, H.H. (South African Journal of Enology and Viticulture, 2016)
Calibration models for Fourier transform mid-infrared (FT-MIR) spectroscopy were developed for the simultaneous quantification of total soluble solids (TSS, measured as °Brix), pH and titratable acidity (TA, expressed as g/L tartaric acid) in South African (SA) grape must. An exploratory data analysis of the FT-MIR spectra of 1170 grape must samples (647 for °Brix, 252 for pH and 271 for TA) was done by principal component analysis, and partial least squares regression was used for the computation of the regression models. The prediction errors for TSS (0.34 °Brix), pH (0.04 units) and TA (0.51 g/L) provided analytical data of satisfactory accuracy. The evaluation of readyto- use global calibrations to quantify these three parameters in SA samples presented standard error of prediction (SEP) values of 0.46°Brix, 0.10 pH units and 3.13 g/L for TA. After slope and intercept adjustments of the original global calibration algorithms, the SEP values were reduced to 0.38 °Brix, 0.05 pH units and 0.49 g/L for TA. These results show the necessity for optimisation of the global FT-MIR WineScan calibrations to provide a better fit to samples of South African origin. The results demonstrate that FT-MIR spectroscopy is a useful technique for the rapid quantification of major grape must parameters and for quality control purposes in an industrial cellar.